Looking out looking in : interpersonal communication - Adler, Ronald B.; Towne, Neil. (New York : Holt, Rinehart and Winston, 1987)
This popular text motivates students to improve their interpersonal skills and sharpen their critical understanding of the process of communication. Through thoughtful, diverse examples that include fine art, music, poetry, film, and more, students can consistently see the importance of interpersonal communication and how it affects their society and their lives.
Includes bibliographies and index.
Keywords: Interpersonal communication -- Textbooks; Interpersonal communication; Social interaction